Quantitative stratigraphic volume of Martian lowlands using Noachian crater statistics: new bounds on volcanic effusion and flooding epochs - Salese, Francesco; Hiatt, Eric; Pondrelli, Monica; Hesse, Marc A.; Soldano, Matilda; Fairén, Alberto G. (Frontiers in Astronomy and Space Sciences, 2026)
The thickness and volume of the stratigraphic sequence in Mars’ northern lowlands remain poorly constrained, despite their key role in recording the planet’s geological and paleoclimatic evolution. Reliable thickness estimates are essential because they directly control calculations of volcanic effusion, surface flooding, and associated climate forcing. Here we present a revised volumetric assessment of the lowland stratigraphy - dominated by volcanic infill - based on integrated geological mapping and crater-statistical modeling. Our approach combines crater size–frequency distributions with volumetric reconstructions of buried craters and intercrater plains across both lowland and Noachian highland reference terrains. The results indicate that the minimum cumulative stratigraphic volume is at least three times greater than previous estimates, implying a proportional increase in volcanic outgassing of CO2, H2O, and SO2. These new quantitative conservative bounds provide improved constraints on early Martian volatile budgets and on mid- to late-Noachian atmospheric evolution, with implications for transient climate warming and late-stage lowland flooding.